Male dominance rank, mating and reproductive success in captive bonobos (Pan paniscus) - Marván, Richard; Stevens, J. M; Roeder, A. D; Mazura, Ivan; Bruford, M. W; Ruiter, J. R. de (Folia primatologica, 2006)
In the recent past, application of DNA genotyping techniques has enabled researchers to more accurately test relationships between dominance rank (DR), mating success (MS) and reproductive success (RS). Paternity studies often reveal that reproductive outcome does not always correlate with male DR and/or MS and thus open room for discussion and interpretation of alternative reproductive tactics of both sexes. In this study, we analysed male DR, MS and RS in a group of bonobos at Twycross Zoo (UK). Genetic relationships were determined using 8 tetrameric microsatellite loci. Despite clear and asymmetric dominance relationships, analysed using normalised David's scores based on a dyadic index of dominance among the group's 3 mature males, we found that the most dominant male did not sire the most offspring. In fact, both infants conceived during the observation period were found to be sired by the lower-ranking males. Although the alpha male had almost exclusive mating access to one of the females during the time she was showing a maximal anogenital swelling, her infant was sired by the lowest-ranking male who mostly mated with her when outside the maximal swelling period. This result suggests that either sperm competition operates and/or ovulation is decoupled from the phase of maximal anogenital swelling which could allow greater female choice. Copyright 2006 S. Karger AG, Basel.
Keywords: Social Behavior; Sexual Behavior, Animal; Fertility; paternita; Male; sociální dominance; mikrosatelitní repetice; Reproduction; Paternity; DNA fingerprinting; Animals, Zoo; DNA Fingerprinting; mužské pohlaví; sexuální chování zvířat; rozmnožování; fertilita; Microsatellite Repeats; Animals; zvířata v ZOO; ženské pohlaví; zvířata; Social Dominance; DNA; Pan paniscus; sociální chování; Female